Shortcuts, Strategies and General Patterns in a Process Study of Nine Professionals - Asadi, Paula; Séguinot, Candace (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractTo date, most process studies have had to get around the problem of duplicating the working environment of professional translators. In fact, the definition of professionalism itself has varied. This study was designed specifically to focus on the strategies of a large group of professionals all from the same workplace. The research involved nine translators in the linguistics department of one pharmaceutical company working on the kind of text that required their specialized experience. It was hoped that if there were experience-related or text-specific strategies shared by translators in the same institutional environment, they would surface either in the record of the translating process or in the think-aloud or retrospective protocols.